Epidemiological study of Setaria equina infection in donkeys: Athmar .K. AL-Azawi , Amer Rasool Fadhl and Shahela Rasool Fadhl - AL-Azawi, Athmar K. (The Iraqi Journal of Veterinary Medicine, 2012)
Autopsy study of 218 (106 male and 112 female) animals slaughtered in Baghdad ( Al-ZAWRA ) Zoo, of central Iraq (Diyala, Wasit, Baghdad) .The total infection rate of Setaria equina was 11.9% and the highest infection rate (22.2%) was recorded in October, where is no infection in January, February and August. It has been observed that the high infection rate (14.5%) during the months of spring and autumn (18.8%) and decrease in winter and summer 3.6% and 10%. Female donkeys with a higher proportion (13.5%) than male10.3% respectively differences ( P < 0.05 ).Worm intensity ranged between 1-6 worm and was shown high worm burden in Autumn and Spring fallowed by Summer and finally Winter seasons, which no infection was recorded in some months of it